PERLINDUNGAN HUKUM TERHADAP PENGURUS SERIKAT PEKERJA ATAS TINDAKAN PELANGGARAN PERJANJIAN KERJA BERSAMA OLEH PERUSAHAAN - Yovita Putri Hardiani; Dipo Wahyoeno (Gapenas Publisher, 2022)
Industrial Relations is a relationship that occurs between a company and a labor union consisting of management and members of a trade union based on deliberation for consensus based on the 1945 Constitution of the Republic of Indonesia and Pancasila as the basis of Indonesian state law, consensus agreement is referred to as an object agreement in the form of a collective work agreement , the object is a regulation/guideline in industrial relations, so an agreement is required between the union officials and the companies involved in the collective labor agreement process. with the interests of each party for parties interested in welfare and the rule of law. The type of research used in this study is normative legal research by conducting research on legal norms in force in Indonesia related to the legal issues raised. The results of this study indicate that in terms of legal protection for union officials, it must be based on legal rules relating to labor laws and regulations, which include Law no. 21 of 2000 concerning Labor Unions, Law no. 13 of 2003 concerning Manpower, PP NO 35 of 2021 concerning Work Agreements for Specific Time, Outsourcing, Working Time and Rest Time, and Termination of Employment, meaning that this protection includes the rights of trade unions which may not violate the substance of collective employment. agreements governing the provisions of labor laws and regulations